2013
DOI: 10.1007/s10646-013-1157-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzo(a)pyrene on differentially expressed genes and haemocyte parameters of the clam Venerupis philippinarum

Abstract: In this study a suppression subtractive hybridisation method was employed to identify differentially expressed genes of the clam Venerupis philippinarum exposed to benzo(a)pyrene (BaP). Nineteen known transcripts and seven predicted proteins were found from the subtractive cDNA library of the clam, which could provide more sequence information for further study. Seven of the differentially expressed genes were selected for mRNA expression analysis. Real-time PCR analysis revealed that the expression level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…On the other hand, B[a]P transferred by microplastics clearly inhibited the phagocytosis activities of coelomocytes of exposed ragworms. Similar conclusions are drawn by Gopalakrishnan et al (2011) in hemocytes of the gastropod abalone H. diversicolor, by Liu et al (2014) in hemocytes of the clam V. philippinarum as well as by Danion et al (2011) in hemocytes of sea bass D. labrax exposed to B[a]P. According to these authors the immunosuppressive effects of B[a]P could be explained by the substantial disruption of sub cellular processes and organelle's functioning of the immune system's cells in the exposed organism. On the other hand, none of the exposure conditions induced a significant release of lysozyme thus supporting some previously reported conclusions that in hemocytes of invertebrates, the assessment of a sole parameter cannot be considered as entirely illustrative of immunocompetence (Ciacci et al, 2012).…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, B[a]P transferred by microplastics clearly inhibited the phagocytosis activities of coelomocytes of exposed ragworms. Similar conclusions are drawn by Gopalakrishnan et al (2011) in hemocytes of the gastropod abalone H. diversicolor, by Liu et al (2014) in hemocytes of the clam V. philippinarum as well as by Danion et al (2011) in hemocytes of sea bass D. labrax exposed to B[a]P. According to these authors the immunosuppressive effects of B[a]P could be explained by the substantial disruption of sub cellular processes and organelle's functioning of the immune system's cells in the exposed organism. On the other hand, none of the exposure conditions induced a significant release of lysozyme thus supporting some previously reported conclusions that in hemocytes of invertebrates, the assessment of a sole parameter cannot be considered as entirely illustrative of immunocompetence (Ciacci et al, 2012).…”
Section: Discussionsupporting
confidence: 65%
“…The abundance of C1qDC transcripts as well as C-type lectin and fibrinogenrelated (FREPs) transcripts in M. galloprovincialis supports their role as pathogen recognition receptors (PRRs) . Nevertheless, factors other than PAMPs are somehow able to trigger the expression of C1qDC genes, such as the exposure to nanoparticles, heavy metals and benzo(a)pyrene Liu et al, 2014aLiu et al, , 2014bMaria et al, 2013). C1qDC transcripts have been detected in bivalve hemocytes (Gestal et al, 2010;Liu et al, 2014a;Oliveri et al, 2014) and a C1qDC protein was reported as the most abundant component of the extrapallial fluid in Mytilus edulis (Hattan et al, 2001;Yin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants in the marine environment, which possess immunotoxic characteristics, carcinogenic and mutagenic [7,56], such as which can disrupt the immune defenses of Crassostrea gigas [5], Pecten maximus [32], Haliotis diversicolor [27], Mytilus edulis [33] and Venerupis philippinarum [48]. PAHs occur in crude petroleum oil or as a result of incomplete combustion and have been considered priority pollutants by the U.S. Environmental Protection Agency [38].…”
Section: Introductionmentioning
confidence: 99%